Urgensi Peraturan Bentuk Badan Hukum Serta Mekanisme Penggabungan dan Pengambilalihan Klub Sepak Bola Di Indonesia (RechtJiva, 2024)
This research examines regulatory challenges concerning the legal structure and the merger and takeover processes of professional soccer clubs in Indonesia. The absence of legal certainty regarding the legal form of football clubs and the corresponding merger/takeover mechanisms poses a threat to sportsmanship principles, particularly as the national football industry advances towards greater professionalism. Then the writing of this thesis uses a normative juridical method with a statutory approach method, a comparative approach. Primary, secondary, and tertiary legal materials obtained by the author will be analyzed using systematic and grammatical interpretation methods. the author gets an answer to the existing problem that it is necessary to establish a regulation by PSSI by cooperating with the government which specifically regulates the form of a limited liability company for clubs and the mechanism for merging and taking over professional football clubs in Indonesia so as to provide legal certainty for football clubs as an important pillar in the development of the football industry. Therefore, the regulatory construction that the author can propose based on an analysis of existing regulations and a comparative study with regulations related to ownership of football clubs in England is to make laws and regulations regarding the obligation of clubs to be incorporated as limited liability companies and the mechanism for mergers and takeovers specifically of football clubs can be by prohibiting mergers between two football clubs in Indonesia that are in different league castes and related to the regulation of takeover stages can be adopted from England.